Formal methods : foundations and applications : 21st Brazilian Symposium, SBMF 2018, Salvador, Brazil, November 26-30, 2018, Proceedings /: foundations and applications : 21st Brazilian Symposium, SBMF 2018, Salvador, Brazil, November 26-30, 2018, Proceedings. (2018) - Unknown
No abstract available